Selenium-Containing Polysaccharides—Structural Diversity, Biosynthesis, Chemical Modifications and Biological Activity - Sandra Górska; Anna Maksymiuk; Jadwiga Turło (Applied Sciences, 2021)
Selenosugars are a group of sugar derivatives of great structural diversity (e.g., molar masses, selenium oxidation state, and selenium binding), obtained as a result of biosynthesis, chemical modification of natural compounds, or chemical synthesis. Seleno-monosaccharides and disaccharides are known to be non-toxic products of the natural metabolism of selenium compounds in mammals. In the case of the selenium-containing polysaccharides of natural origin, their formation is also postulated as a form of detoxification of excess selenium in microorganisms, mushroom, and plants. The valency of selenium in selenium-containing polysaccharides can be: 0 (encapsulated nano-selenium), IV (selenites of polysaccharides), or II (selenoglycosides or selenium built into the sugar ring to replace oxygen). The great interest in Se-polysaccharides results from the expected synergy between selenium and polysaccharides. Several plant- and mushroom-derived polysaccharides are potent macromolecules with antitumor, immunomodulatory, antioxidant, and other biological properties. Selenium, a trace element of fundamental importance to human health, has been shown to possess several analogous functions. The mechanism by which selenium exerts anticancer and immunomodulatory activity differs from that of polysaccharide fractions, but a similar pharmacological effect suggests a possible synergy of these two agents. Various functions of Se-polysaccharides have been explored, including antitumor, immune-enhancement, antioxidant, antidiabetic, anti-inflammatory, hepatoprotective, and neuroprotective activities. Due to being non-toxic or much less toxic than inorganic selenium compounds, Se-polysaccharides are potential dietary supplements that could be used, e.g., in chemoprevention.